Development of e-worksheets using Canva-Heyzine flipbook on excretory system material for eleventh graders - Afreni Hamidah; Putri Setia Asni Ningrum; Raissa Mataniari (University of Muhammadiyah Malang, 2025)
This study aims to develop e-worksheet teaching materials on the excretory system, assess their feasibility, analyze teacher responses, and evaluate trial results using the e-worksheet. The research follows a Research and Development (R&D) approach, employing the ADDIE development model. The study was conducted at SMAN 8 Tanjung Jabung Timur, involving two biology teachers and class XI IPA students, divided into small groups (6 students) and large groups (27 students). Both qualitative and quantitative data were collected using questionnaires. The validation results indicate that the material experts rated the e-worksheet at 91.25% (